2000
DOI: 10.18388/abp.2000_4015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stress on the life span of the yeast Saccharomyces cerevisiae.

Abstract: A correlation is known to exist in yeast and other organisms between the cellular resistance to stress and the life span. The aim of this study was to examine whether stress treatment does affect the generative life span of yeast cells. Both heat shock (38 degrees C, 30 min) and osmotic stress (0.3 M NaCl, 1 h) applied cyclically were found to increase the mean and maximum life span of Saccharomyces cerevisiae. Both effects were more pronounced in superoxide dismutase-deficient yeast strains (up to 50% prolong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…It has been reported that osmotic stress caused by 0.3 M (1.75% NaCl w/v) NaCl and for a time period of 1 hour may prolong the life span of yeasts. 26 The relationship between temperature and osmotic stress regarding osmotic tolerance of cells and viability has previously been reported. Under osmotic pressure of 49.2 MPa cell viability was close to 94% at a temperature of 23°C, but under higher osmotic pressure of 99 MPa the viability decreased dramatically to 25%.…”
Section: Resultsmentioning
confidence: 95%
“…It has been reported that osmotic stress caused by 0.3 M (1.75% NaCl w/v) NaCl and for a time period of 1 hour may prolong the life span of yeasts. 26 The relationship between temperature and osmotic stress regarding osmotic tolerance of cells and viability has previously been reported. Under osmotic pressure of 49.2 MPa cell viability was close to 94% at a temperature of 23°C, but under higher osmotic pressure of 99 MPa the viability decreased dramatically to 25%.…”
Section: Resultsmentioning
confidence: 95%
“…It has been reported that osmotic stress caused by 0.3 M (1.75 % w/v) sodium chloride for a time period of 1 h may prolong the life span of yeasts (24). The relationship between temperature and osmotic stress regarding osmotolerance and yeast cell viability has previously been reported (26).…”
Section: Laboratory-scale Fermentationsmentioning
confidence: 99%
“…Excess amount of ethanol has been reported to cause mitochondrial DNA damage and degrades bio membranes in yeast cells (Swiecilo et al, 2000). Ethanol can dissolve fatty acid constituents of the cell membranes; disrupt cytoplasmic membrane rigidity (Osho, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Approaches to measure ethanol tolerance involve determination of ethanol effects on cell growth, fermentation ability, viability and batch culture performance (Ekunsanmi and Odunfa, 1990). High ethanol tolerant strains are able to extend the process of fermentation for longer time and produce distinct products in the presence of ethanol (Swiecilo et al, 2000). Resistant strains to ethanol stress have other abilities like resistance to other stresses such as osmotic pressure and oxidative and heat (Swiecilo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation